2020
DOI: 10.18203/2394-6040.ijcmph20202536
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness among nursing students regarding the COVID-19: a cross sectional study

Abstract: Background: The health care providers are at the front line of the outbreak response of current pandemic of COVID-19 and exposed to hazards that put them at risk of infection. Rapid spread of the COVID-19 pandemic has become a major cause of concern for the healthcare profession in all over the world. All health care professional must stay aware of the latest information on the COVID-19 outbreak. This research paper deals with the knowledge and awareness about COVID-19 among nursing students.Methods: By non-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
2
8
1
1
Order By: Relevance
“…As well as after graduation, nurse's neglect reading updating their professional knowledge, it was expected to find such low level of knowledge. The present study findings are in congruence with Joshi, et al (2020) [12] who studied" Knowledge and awareness among nursing students regarding the COVID-19: a cross sectional study", who concluded that, the study participants showed adequate basic knowledge and awareness of COVID-19. There is a strong need to implement periodic educational interventions and training programs on infection control practices and other updates of COVID-19 across all healthcare professions including nursing students.…”
Section: Discussionsupporting
confidence: 92%
“…As well as after graduation, nurse's neglect reading updating their professional knowledge, it was expected to find such low level of knowledge. The present study findings are in congruence with Joshi, et al (2020) [12] who studied" Knowledge and awareness among nursing students regarding the COVID-19: a cross sectional study", who concluded that, the study participants showed adequate basic knowledge and awareness of COVID-19. There is a strong need to implement periodic educational interventions and training programs on infection control practices and other updates of COVID-19 across all healthcare professions including nursing students.…”
Section: Discussionsupporting
confidence: 92%
“…83.54% participants were aware about concept of hand hygiene and 83.37% were well aware of PPE for suspected or confirmed COVID-19 cases. 6…”
Section: Discussionmentioning
confidence: 99%
“…10 In another COVID-19 knowledge related study by Joshi et al at Telangana state in India showed that 75.6% participants had high level of understanding regarding the novel disease. 8 A survey among medical and allied health care students across India found that the participants had adequate knowledge regarding the new disease. 11 An online questionnaire based survey by Jose et al among the pharmacy students in Kerala showed that >70% of the participants had good understanding about the transmissibility of coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…The study also proved that there is a clear need for regular orientation and training programs to improve and update knowledge regarding COVID-19 infections and prevention strategies. 8 Our study aims at exploring the knowledge about the current treatment modalities of COVID-19, among the final year medical students and interns across the country. The knowledge about the proper precautionary measures, dead body disposal and the information seeking behaviour among the students is also being evaluated.…”
Section: Introductionmentioning
confidence: 99%